ECONOMIC PRESSURE MODERATES CORPORATE GROWTH AND CORPORATE GOVERNANCE ON CARBON EMISSION DISCLOSURE - Rarasasi Ribka Redonoarsi; Nofryanti; Holiawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the effect of economic pressure moderation on corporate growth and corporate governance on carbon emission disclosure. This study focuses on companies that are members of the KOMPAS100 index on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This study uses an associative quantitative approach. The sample determination was carried out by purposive sampling technique and data analysis using a panel data regression equation. The results of this study are that company growth and corporate governance have an effect on the disclosure of carbon emissions while economic pressure has no effect on the disclosure of carbon emissions. Economic pressures also cannot moderate corporate growth and corporate governance against carbon emission disclosure.